2020
DOI: 10.1007/s40211-020-00359-5
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in medical students

Abstract: Only a small number of studies have examined the relationship between medical students and burnout syndrome. In Salzburg, Paracelsus Private Medical University (PMU) offers a 5-year medical program instead of the regular 6 years of medical studies. Due to the tight schedule and heavy workload, the stress level of students is high. The purpose of this study was to determine whether PMU students show burnout symptoms. Three surveys were conducted: at the beginning of the academic year (T1, December 2009), at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
1
21
0
6
Order By: Relevance
“…Regarding demographic data, there is no significant association of gender with a burnout in our study which is similar to the findings of some prior studies [ 30 – 32 ] but contrary to the studies which show high burnout in females compared to males [ 12 , 33 ]. Also, no significant association was found between different age groups of students, which is similar to the findings of a previous study done by Dyrbye (2014) [ 18 ] and contrary to the findings of the previous study by O’Connor (2018) [ 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding demographic data, there is no significant association of gender with a burnout in our study which is similar to the findings of some prior studies [ 30 – 32 ] but contrary to the studies which show high burnout in females compared to males [ 12 , 33 ]. Also, no significant association was found between different age groups of students, which is similar to the findings of a previous study done by Dyrbye (2014) [ 18 ] and contrary to the findings of the previous study by O’Connor (2018) [ 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…The studies involved in the analysis used the MBI and Copenhagen Burnout Inventory (CBI). A more recent study involving 250 medical students in Austria, which used MBI, found a close result of 47,8% (Thun-Hohenstein et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…Egy pakisztáni egyetemen folytatott vizsgálat (Iqbal et al, 2020) alapján az első-és másodéves orvostanhallgatók között a distressz előfordulása 100%-os. A mentális egészségügyi adatok epidemiológiája pedig azt mutatja, hogy a medikusok több mint 20%-a pszichés zavarban szenved és/vagy mentálhigiénés problémákkal küzd (Thun-Hohenstein et al, 2020).…”
Section: Orvostanhallgatók Pszichológiai Ellátásaunclassified
“…Számos vizsgálat tanulmányozta az orvosok kiégésének eredetét, és az elmúlt 10 évben egyre több kutatás számol be arról, hogy a burnout jelenség már az orvosi egyetemen elkezdődhet (Chunming et al, 2017;Thun-Hohenstein et al, 2020). Egyes tanulmányok alapján a medikusok megközelítőleg fele szenvedhet kiégéstől (Enoch et al, 2013).…”
Section: Kiégés Az Orvostanhallgatók Körébenunclassified